1984
DOI: 10.1007/bf00237997
|View full text |Cite
|
Sign up to set email alerts
|

Roles of glabrous skin receptors and sensorimotor memory in automatic control of precision grip when lifting rougher or more slippery objects

Abstract: To be successful, precision manipulation of small objects requires a refined coordination of forces excerted on the object by the tips of the fingers and thumb. The present paper deals quantitatively with the regulation of the coordination between the grip force and the vertical lifting force, denoted as the load force, while small objects were lifted, positioned in space and replaced by human subjects using the pinch grip. It was shown that the grip force changed in parallel with the load force generated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
1,088
10
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,490 publications
(1,162 citation statements)
references
References 31 publications
62
1,088
10
2
Order By: Relevance
“…the observed grip force minus the minimum grip force required to prevent slippage) is also greater for heavy and slippery objects. Indeed, Johansson and Westling (1984) have observed that the ratio of excess to minimum grip force is approximately constant across all objects. They have suggested that the excess grip force guards against random fluctuations in the motor system and that grip force is scaled with load force in order to economize effort.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…the observed grip force minus the minimum grip force required to prevent slippage) is also greater for heavy and slippery objects. Indeed, Johansson and Westling (1984) have observed that the ratio of excess to minimum grip force is approximately constant across all objects. They have suggested that the excess grip force guards against random fluctuations in the motor system and that grip force is scaled with load force in order to economize effort.…”
Section: Introductionmentioning
confidence: 94%
“…For example, when an object is lifted, grip force increases simultaneously with load force prior to lift-off (Johansson and Westling 1984). The rate of increase of grip force and the final grip force depend on the object's weight and its surface texture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of finger interaction have focused on the production of adequate gripping force (Johansson and Westling 1984;Flanagan and Wing 1995;Burstedt et al 1999;Santello and Soechting 2000;Nowak and Hermsdorfer 2005). Only a handful of studies explicitly addressed the rotational action by the hand (e.g., Johansson et al 1999;Latash et al 2004).…”
Section: Multi-finger Synergies Stabilizing Rotational Hand Actionmentioning
confidence: 99%
“…The pinch force modifications were in phase with the changes in load force [19]. Slips rarely occurred as the pinch force exceeded the minimum force required to prevent slippage according to a slip margin determined by the skin object friction [20].…”
Section: Discussionmentioning
confidence: 99%